Curriculum And Learning For Down Syndrome Children Who Have Reading Difficulties In Inclusive School - Ervina Yuliandini; Endang Rochyadi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Inclusive schools are educational institutions that accommodate all students, both normal students, and students with special needs, to get educational services according to their needs to create a friendly and fun learning atmosphere. Carrying out learning in inclusive schools, of course, requires a curriculum. Curriculum and learning are part of the education system that cannot be separated and interrelated. This study aims to develop a curriculum and learning program for students with special needs Down syndrome in grade 1 in inclusive elementary schools who experience problems in the early reading aspect because one of the prerequisites in early reading has not been met. This study uses research methods with a qualitative approach. Qualitative research is used to explore student profile information and learning profiles which are then used as the basis for developing curriculum and learning programs. The results of this study are to obtain a learning program that is to the needs of students obtained from the process of aligning the curriculum. Thus, it is recommended that teachers harmonize the curriculum based on the results of the assessment so that curriculum and learning programs are obtained that are in bye needs of students.